2013
DOI: 10.4322/rbeb.2013.028
|View full text |Cite
|
Sign up to set email alerts
|

Current perception threshold and reaction time in the assessment of sensory peripheral nerve fibers through sinusoidal electrical stimulation at different frequencies

Abstract: Introduction: The Perception Sensory Threshold (ST) for sinusoidal current stimuli at 5, 250, and 2,000 Hz is commonly used in the assessment of peripheral nerve fibers (C, Aδ, and Aβ, respectively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 24 publications
2
21
0
1
Order By: Relevance
“…Responses due to felt sensations in each block were categorized as suggested by Martins et al [14], in which blocks that contained words related to both groups (thin and thick fibers) are called BOTH, related to thin fibers THIN, and to thick fibers THICK. Thus, evaluation of perceived sensations -and indirect fiber activation -was performed by each group's percent change due to stimulus intensity increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Responses due to felt sensations in each block were categorized as suggested by Martins et al [14], in which blocks that contained words related to both groups (thin and thick fibers) are called BOTH, related to thin fibers THIN, and to thick fibers THICK. Thus, evaluation of perceived sensations -and indirect fiber activation -was performed by each group's percent change due to stimulus intensity increase.…”
Section: Discussionmentioning
confidence: 99%
“…The ST was evaluated through the current source Neurostim equipment [13,14]. Electrodes used for electrical stimulation were gold planar concentric (anode as a rim of 9-7 mm diameter and cathode as a 2 mm disc), suggested to have better specificity for Aβ-fiber stimulation, due to its increased focality and relative deepened electrical current density [16,22].…”
Section: St Evaluationmentioning
confidence: 99%
“…During the past two decades, studies have shown that selectively activating Aβ-fibers ought to be attainable by using sinusoidal electrical stimulation of high frequencies, such as 2 kHz and 3 kHz, at the sensory threshold (ST) level as a psychophysical evaluation [13][14][15][16][17]. This is usually assessed through subjective questionnaire answers, where participants have to decide on words from a given list, that describe best the sensations felt after stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…This is usually assessed through subjective questionnaire answers, where participants have to decide on words from a given list, that describe best the sensations felt after stimulation. Thus, it is a forced-choice paradigm that highly depends on individual's cognitive state, and whether this type of stimuli elicits conscious tactile-related responses cortically was not yet assessed [9,13,14,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation